Students’ Perception of Duolingo Application on Mastering Vocabulary - Cinta Taufika Anandra; Maryati Salmiah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The purpose of this study is to ascertain which aspects of the language have improved as a result of using the Duolingo app and how English majors view its utility as a tool for language acquisition. In this study, a qualitative research design is used. Ten junior high school students in the second grade who had been using the Duolingo app for longer than seven days participated in this study. Students completed questionnaires and conducted interviews in order to collect data. The research's conclusions show that most students concur that using the Duolingo app can facilitate English language learning. According to the results of the questionnaires and interviews conducted by the researchers, students believed that the Duolingo app had a lot of beneficial effects on their language learning, including increasing their motivation to learn, practicing, and using their language skills in everyday situations. Aside from that, students who used the Duolingo app made improvements in a variety of language domains, including syntax and pronunciation proficiency, vocabulary knowledge and ease of memorization, and process facilitation of the English language proficiency improvement process. Future researchers are the target audience for this, according to the research findings. In order to explore more aspects of the Duolingo application and its use in English language instruction, researchers intend to conduct more thorough studies with a larger sample size in the future.